How Well do You Know Me: Culture and the Self - Akande, Will A. (Sociologija. Mintis ir veiksmas, 2010)
In a series of studies we investigated the validity of PASCI and explored the congruence in five geographical entities. The present study has been conducted with the aim to know the self-esteem of participants who were students. Due to inconsistent and indeterminate findings, business researchers and cross-cultural scholars have failed to take into account possible interaction between culture/gender and social behaviour (self ). Through analyses of variance, we provide evidence, that nationality yielded highly significant levels of self-esteem. This result was interpreted as adding credence to the view that studying the self is important across cultures. The findings are mirrored in the individualism-collectivism dimensions and reasons for these findings are discussed. In addition, suggestions for future research may lead to Lithuanian data that might be valued as an important mediating factor that can influence other important psychological and behavioural outcomes such as job satisfaction and employee retention in organizations.